(untitled) (Bangladesh Journal of Urology, 2022)
Back ground: The incidence of renal calculi is rising and more patients are presenting with small renal calculi. The treatment options for renal calculi (d”2 cm) are ESWL, percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS). The development of minimal invasive surgery for the treatment of renal calculus has led to an increase in success rates and, at the same time, has decreased the morbidity associated with these treatments. Objective: The study aimed to evaluate outcome of retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy in the treatment of upper calyceal stone of d”2 cm in diameter. Methods: 60 Patients with radiopaque upper calyceal stone (d”2 cm) were admitted and underwent RIRS (Group A) & PCNL (Group B) in Urology department as per inclusion and exclusion criteria by purposive sampling (30 patients in each group). Complete clinical evaluation including history, physical examination, relevant examinations & laboratory investigations were performed. Result: Mean age was 37.23±11.59 years (range 18-62years) in group A and 40.10±11.49 (range 18-65 years) in group B. Mean operative time was significantly lower in group A (90.13 +/- 18.79 min) than group B (107.36 +/- 16.4 min) (p <0.05). Mean volume of irrigation fluid used during surgery, mean drop in the postoperative hemoglobin concentration, hospital stay, mean VAS score at 8 hours & 24 hours after operation were significantly lower in RIRS group than PCNL group (p< 0.05). We achieved a stone clearance of 90.00% in the RIRS group and 96.67% in the PCNL group. The difference in stone clearance in two groups was not statistically significant (p=0.30). Conclusion: The study concluded Retrograde intrarenal surgery (RIRS) in the treatment of upper calyceal stone of d”2cm in diameter is a feasible, effective and safe treatment option. Given the added morbidity in PCNL, RIRS should be considered standard therapy in these patients. Bangladesh J. Urol. 2021; 24(1): 99-104